Immunohistochemical analysis of Langerhans cells in chronic gingivitis using anti-CD1a antibody - Shweta Jaitley; Sriram Gopu; Saraswathi T Rajasekharan; Balasundaram Sivapathasundaram (Wolters Kluwer Medknow Publications, 2014)
Background: The Langerhans cells (LCs) are dendritic cells (DCs) which belong to the group of antigen presenting cells (APCs). Their function is to recognize the antigen, capture it, and present it to the T lymphocytes; thus initiating an early immune response. The antigen presenting functional LCs may play an important part in initiation and development of gingivitis. The aim of this study was to analyze the density, intraepithelial distribution, and morphology of LCs in gingival epithelium among different age groups with chronic gingivitis and to compare it with that of normal gingiva. Materials and Methods: Immunohistochemistry (IHC) was performed to study LCs in normal gingival epithelium (n = 10) and gingival epithelium in chronic gingivitis (n = 30) using anti-CD1a antibody. Mann Whitney U test was performed to compare the density of LCs in normal gingiva with chronic gingivitis. The distribution of LCs in various layers of the epithelium within the three age groups was analyzed using Kruskal-Wallis test. P value less than 0.05 was considered as significant. Results: The density of LCs in chronic gingivitis was significantly higher then that of normal gingiva. Comparing different age groups, the younger individuals had more number of LCs which were located in the superficial layers of gingival epithelium. In chronic gingivitis, higher number of LCs were located in deeper layers when compared with that of normal gingiva. Three morphological types of CD1a positive LCs were observed in normal gingiva, out of which the density of LCs with branched dendritic processes was highest in normal gingiva. Conclusion: The LCs showed variable number, location, and morphology which indicated their adaptation for function in chronic gingivitis.